Positive correlation between fatty liver index and hyperuricemia in hypertensive Chinese adults: a H-type hypertension registry study - Yu, Chao; Zhou, Xinlei; Wang, Tao; Zhu, Lingjuan; Zhou, Wei; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2023)
Background: Few studies have examined the relationship between fatty liver index (FLI) and hyperuricemia (HUA). This study explores the relationship between FLI and HUA in hypertensive patients. Methods: A total of 13,716 hypertensive subjects were included in the current study. FLI, a simple index calculated from triglycerides (TG), waist circumference (WC), body mass index (BMI), and γ -glutamyltransferase (GGT), was used as a useful predictor of nonalcoholic fatty liver disease (NAFLD) distribution. HUA was defined as serum uric acid ≥ 360 μmol/L for females and ≥ 420 μmol/L for males. Results: The mean value of total FLI was 31.8 ± 25.1. Multiple logistic analyses revealed a significant positive correlation between FLI and HUA (OR, 1.78; 95% CI: 1.69–1.87). A subgroup analysis demonstrated that the correlation between FLI (< 30 vs. ≥ 30) and HUA was significant in both sexes (P for interaction = 0.006). Further analyses stratified by sex indicated a positive correlation between FLI and HUA prevalence among male and female subjects. However, the correlation between FLI and HUA was stronger in female subjects than in males (male: OR, 1.70; 95% CI: 1.58–1.83; female: 1.85; 95% CI: 1.73–1.98). Conclusion: This study demonstrates a positive correlation between FLI and HUA in hypertensive adults, but stronger in females than males.